Exploring the Effect of Asperity Order on Mechanical Character of Joint Specimen from the Perspective of Damage - Zhouhao Yuan; Yicheng Ye; Binyu Luo (Geofluids)
The joint morphology is multiscale. The effect of each asperity order on the mechanical properties of joints is different. The shear mechanical properties of joint specimens are related to its surface damage characteristics. At present, there are still few studies on the effect of roughness on the shearing mechanical properties of joint from the perspective of damage of each asperity order. In this paper, the standard roughness profile was chosen as initial morphology. The standard roughness profile was decomposed into waviness and unevenness by the method combine the ensemble empirical mode decomposition (EEMD) and the cut-off criterion. Then, the joint specimen which contains waviness and unevenness and the specimen which only contains waviness were prepared by the 3D engraving technology. The 40 sets of joint specimens with different asperity order were subjected to direct shear tests under different normal stresses. Based on the 3D scanning technology and ICP iterative method, the damaged area and the damage volume were calculated. Based on the damage volume data and the acoustic emission (AE) data, the effect of asperity order to the joint mechanical behaviour was studied. The results indicate that (1) under low normal stress, the unevenness plays a control role in the failure mode of the joint specimen. Under low normal stress, the joint surface containing only waviness exhibits slip failure, and the joint surface with unevenness exhibits shear failure. With the increase of the normal stress, the failure mode of the specimen containing only waviness changes from slip failure to shear failure; (2) the unevenness controls the damage degree of the joint specimen. The damaged area, damage volume, AE energy rate, and accumulative AE energy of the joint specimen with unevenness are larger than those of the specimen with only waviness, and this difference increases with the normal stress increase; (3) the difference between the joint specimen with unevenness and specimen with only waviness mainly exists in the prepeak nonlinear stage and the postpeak softening stage. The characteristic parameters of acoustic emission generated in the postpeak softening stage of the joint specimen with unevenness are greater than those of the specimen with only waviness. This phenomenon can be used to explain the stress drop difference at the postpeak softening stage; (4) the AE b value can be used to evaluate the damage of joint specimens. Analysing the damage difference of each asperity order under different normal stresses is of great significance to the analysis of the influence of the morphology of the joint surface on the mechanical properties of the joint.